2022
DOI: 10.3390/pathogens11111310
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genomic Characterisation of Clostridioides difficile from Spinach Fields

Abstract: Despite an increased incidence of Clostridioides difficile infections, data on the reservoirs and dissemination routes of this bacterium are limited. This study examined the prevalence and characteristics of C. difficile isolates in spinach fields. C. difficile was detected in 2/60 (3.3%) of spinach and 6/60 (10%) of soil samples using culture-based techniques. Whole genome sequencing (WGS) analysis identified the spinach isolates as belonging to the hypervirulent clade 5, sequence type (ST) 11, ribotypes (RT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 135 publications
1
0
0
Order By: Relevance
“…An important finding in this report is that the authors observed a similar distribution of ribotypes between clinical, hospital and environmental isolates (RT014/020, 002, 078/126 as most common) with the exception that ribotype 027, which was significantly more common in the clinical isolates compared with the environmental isolates [105]. A recent study detected ST11 (RT078 and RT126) strains in spinach [106]. A very large study covering a wide part of the world (North America (Mexico), Central America (Peru, Guatemala), South America (Brazil), Europe (France, Germany, Italy), and Asia (Taiwan, India)) showed high C. difficile contamination rates (~24%), which were similar for healthcare buildings and non-healthcare buildings.…”
Section: Epidemiologysupporting
confidence: 60%
“…An important finding in this report is that the authors observed a similar distribution of ribotypes between clinical, hospital and environmental isolates (RT014/020, 002, 078/126 as most common) with the exception that ribotype 027, which was significantly more common in the clinical isolates compared with the environmental isolates [105]. A recent study detected ST11 (RT078 and RT126) strains in spinach [106]. A very large study covering a wide part of the world (North America (Mexico), Central America (Peru, Guatemala), South America (Brazil), Europe (France, Germany, Italy), and Asia (Taiwan, India)) showed high C. difficile contamination rates (~24%), which were similar for healthcare buildings and non-healthcare buildings.…”
Section: Epidemiologysupporting
confidence: 60%
“…Furthermore, RT001 and RT014 were one of the most frequently detected in isolates from poultry meat in Germany [19]. RT014 was also detected in soil samples being located next to a dairy farm [45]. RT014 and RT020 were the predominant RT among soil isolates obtained from home gardens in Western Australia [46] and poultry feces [20].…”
Section: Discussionmentioning
confidence: 97%
“…Capillary electrophoresis offers an improved separation of amplified nucleic acid fragments, leading to enhanced sensitivity of the assay compared to traditional agarose electrophoresis [52,55,56]. Therefore, it may lead to relatively fast recognition of CDI hospital outbreaks worldwide [57][58][59] and facilitate antimicrobial resistant strains' elimination [60][61][62][63], including those derived from children [64], the environment, plants and animals [65][66][67][68][69][70][71]. As it has been previously proven, an ineffective decontamination with non-optimal time of exposure or a concentration of sporicidal disinfectants may result in an extensive C. difficile strain transmission [60].…”
Section: Introductionmentioning
confidence: 99%